PENGEMBANGAN LEMBAR KERJA PESERTA DIDIK DENGAN LIVEWORKSHEETS PADA MATA PELAJARAN MATEMATIKA DI SEKOLAH DASAR - Pamungkas, Aan Subhan; Alamsyah, Trian Pamungkas; Alawiyah, Tuti (Universitas Sultan Ageng Tirtayasa, 2023)
ABSTRACTThis study aims to develop student worksheets online by utilizing the liveworksheets platform in mathematics subjects, sub-materials on statistics, collecting and reading data, this study is also to determine the quality of the developed mathematics student worksheets, to determine the teacher's response to student worksheets. mathematics, as well as knowing student responses after using math worksheets with live worksheets. The subjects of this study were 27 fifth grade students at SDN Banjarsari 4. The results of the assessment in this study were getting 85.29% from material experts, 94.00% from media experts, and 90.00% from linguists so that the overall score obtained in the